Compact automated culture machine for human induced pluripotent stem cell maintenance and differentiation - Bando, Kazunori; Yamashita, Hiromi; Tsumori, Motomu; Minoura, Hayase; Okumura, Koji; Hattori, Fumiyuki (Frontiers in Bioengineering and Biotechnology, 2022)
The technologies used to generate human induced pluripotent stem cell (iPSC) from somatic cells potentially enable the wide application of iPSC-derived differentiated cells in industrial research fields as a replacement for animals. However, as highly trained individuals are required to obtain reproducible results, this approach has limited social implementation. In the research field of iPSC, it is believed that documentable information is not enough for reproducing the quality of the differentiated cells. Therefore, automated culture machines for cell processing should make the starting of iPSC-using researches easier. We developed a programmable all-in-one automated culture machine, with dense and compact constitution that fits within a normal biosafety cabinet (200 mm wide, 233 mm height, and 110 mm depth). This instrument was fabricated using novel x-y-z-axes-rail-system, such as an overhead traveling crane, in a factory, which served as the main handling machinery. This machine enabled stable and efficient expansion of human iPSC under the feeder-free condition, without karyotype alterations, and simultaneously differentiated the cells into various cell types, including cardiomyocytes, hepatocytes, neural progenitors, and keratinocytes. Overall, this machine would facilitate the social implementation of human pluripotent stem cells and contribute to the accumulation of sharable knowledge for the standardization of the entire handling processes of iPSC in pharmaceutical, food, and cosmetic research.